PROFIL ANTROPOMETRI ANAK DENGAN PENYAKIT JANTUNG BAWAAN DI RSUP. DR. M. DJAMIL PADANG PERIODE JANUARI 2020 – DESEMBER 2021 - yandika, kevin rayhan; Masnadi, Nice Rachmawati; Rahman, Sukri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Congenital Heart Disease is an abnormality of the heart that is present from birth caused by failure or structural disturbances in the development of the heart in the early phases of fetal development. Congenital heart disease is divided into two types, namely, acyanotic and cyanotic. Children with congenital heart disease can fall into a state of malnutrition. Anthropometric examination is carried out to determine the nutritional status and stature of children with congenital heart disease. This study aims to determine the anthropometric profile of children with congenital heart disease at Dr. M. Djamil Padang. This research is a retrospective descriptive study using medical record data in 2020 - 2021. There were 36 samples of children with a diagnosis of CHD as a sample. The sampling method used the Total Sampling technique. The indicators taken in this study were the type of congenital heart disease, age, gender, nutritional status, and congenital disease. The results showed that most of the pediatric patients with CHD suffered from DSV (61.1%), with an age range of 29 days - 1 year (44.4%), were male (52.8%), suffered from malnutrition (69, 4%), and had short stature (63.9%). The conclusion from this study is that children with CHD are at high risk of suffering from malnutrition and have short hospital stays, so it is necessary to pay attention to nutritional intake in children with CHD